Organizational Capacity Assessment of Herbs, a Rural-Based Farmer Organization in San Pablo City, Laguna, Philippines - Herbert Ticzon (Philippine Association of Institutions for Research, Inc., 2019)
HERBS Inc. is a rural-based organization recently established in San Pablo City, Laguna, the Philippines comprising of farmers who are senior citizens, mostly retired in government service, to formalize training in organic farming, harvesting, and selling products such as chili powder, chili paste, soya milk, and other soy by-products. Records from the City Agricultural Office showed that newly formed farmer's organizations in the past ten years experienced difficulties in management and operations and eventually faced the risk of closure. The study was conducted to assess this organization in its capacity for entrepreneurship for its members to improve their income and uplift their quality of life, thus promoting inclusiveness in our society. Focused Group Discussion using PRA tools such as Livelihood analysis, Venn Diagram, SWOT and TOWS analysis, Problem Tree analysis, and Logical Framework Matrix was used in conducting this study. Results showed that the organization still need further training on organizational competencies and skills to achieve and maintain their goals and objectives. Furthermore, the findings showed the internal and external factors that hinder or stimulate the development of their organization. The Participatory Rural Appraisal has been proven to be effective in assessing organizational capacity; therefore, we recommend its usage in carrying out studies of this nature.